اسلامی تعلیمات کی روشنی میں گداگری کاتحقیقی وعلمی جائزہ : A Research and Scientific Review of Beggaring in the Light of Islamic Teachings - Agha, Syed Muhammad Hanif; Hayatullah, Syed (Al-Irfan, 2024)
Mankind by nature suffers from different types of habits. Some of these habits have good qualities while others contain bad qualities. The good and bad of human habits are sometimes determined by the Sharia and law, respectively. Beggaring is also one of the human habits that have its pros and cons. The purpose of this study is to conduct a research and scientific review of beggaring in the context of Sharia teachings and practices so that the positive and negative aspects of the said habit are highlighted in the light of Islamic teachings. There is no doubt that Islam has taken care of human values as much as it is difficult to find an example. Sharia rules are formulated according to human temperament and physical structure. Due to habits such as begging, a person loses his good skills and society gives rise to various types of crimes.